“Si beau ma queen”: The Speech Construction of Queer Identity Perception in French Social Media - Aprillia Firmonasari (Universitas Gadjah Mada, 2021)
Queer as a gender identity draws varying responses globally. In French the representation of Queer in various social media has raised a number of public’s perceptions, both in positive and negative manners. This perception does not only concern about French linguistic issues, but also its socio-cultural issues. This study puts an emphasis on the widely-used speech patterns showing the public perception on both French queer and immigrant queers posted on French social media. Further, it also examines the socio-cultural context that influences the social contact and relation between the public and the phenomenon of Queer as a subject in social media. This study uses interactionist approach and gender-based critical discourse analysis based on the theory of interpersonal contact between groups proposed by Gordon Allport. In explaining the phenomenon, the researcher employs qualitative content analysis and uses criticial discourse analysis and gender-based criticism. The data are collected from both French and immigrant queers’ posts on social media in 2020. The results show that French queers are perceived to have equal standing position with other French people as they are considered as a part of French society. The result also shows that unlike French queer, the immigrant-descent queer are considered to have inequal position with French society due to the immigrant’s negative stereotype as the trigger of social problems in France.